Posttraumatic stress and medication adherence in pediatric transplant recipients. Issue 3 (20th December 2021) - Duncan‐Park, Sarah; Danziger‐Isakov, Lara; Armstrong, Brian; Williams, Nikki; Odim, Jonah; Shemesh, Eyal; Sweet, Stuart; Annunziato, Rachel
Abstract : Adolescent transplant recipients may encounter a range of potentially traumatic events (PTEs) pre‐ and posttransplant, yet little is known about the relationship between posttraumatic stress symptoms (PTSS) and medication adherence in this population. In the present study, adolescent recipients and caregivers completed psychosocial questionnaires at enrollment. Outpatient tacrolimus trough level data were collected over 1 year to calculate the Medication Level Variability Index (MLVI), a measure of medication adherence. Nonadherence (MLVI ≥2) was identified in 34.8% of patients, and most (80.7%) reported ≥1 PTE exposure. Levels of PTSS indicating likely posttraumatic stress disorder (PTSD) were endorsed by 9.2% of patients and 43.7% of caregivers. PTSS and MLVI were significantly correlated in the liver subgroup ( r  = .30, p  = .04). Hierarchical multivariable linear regression analyses revealed overall patient PTSS were significantly associated with QoL ( p  < .001). PTEs are common in adolescent recipients; a minority may meet criteria for PTSD. PTSS screening to identify nonadherence risk requires further investigation and addressing PTSS may improve QoL. Caregivers appear at greater risk for PTSD and may require their own supports. The study was approved by each participating center's Institutional Review Board. Abstract : This multisite investigation of pediatric solid organ recipients found that posttraumatic stress symptoms (PTSS) are correlated with tacrolimus nonadherence in liver recipients, that caregivers compared to their children display more PTSS, and that PTSS are associated with lower recipient quality of life.